Consulting Engineer - a new profession in the field of construction of Ukraine - Galinskyi О. (Ways to Improve Construction Efficiency, 2019)
The article deals with the organizational and legal aspects of the activity of the consulting engineer - a new profession in the field of construction; qualification requirements for the relevant categories and an indicative list of services that an consulting engineer can provide to the customer (investor) of construction. It is noted that the qualification of the consulting engineer must be confirmed by a "third party" - the body for certification of the personnel of the construction industry after the training of a specialist in the training center; whose competence is confirmed by the certification body. The order of certification of the consulting engineer is given.